2015
DOI: 10.1177/183693911504000402
|View full text |Cite
|
Sign up to set email alerts
|

‘Better Beginnings has made me make reading part of our everyday routine’: Mothers' Perceptions of a Family Literacy Program Over Four Years

Abstract: THIS PAPER EXPLORES THE Better Beginnings family literacy program over a period of four years through the eyes of mothers of young children from four diverse communities. It focuses on their reported perceptions of the program and related practices. Better Beginnings, which involves strong cooperation between health professionals, local government and public libraries, was developed by the State Library of Western Australia to encourage parents to share books, songs and rhymes with their babies and young child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…In addition to reading more often, parents in the intervention group reported significantly greater comfort reading to their infants relative to the control group, and also assigned higher importance to shared reading at this age. These findings are consistent with our hypothesis and also with existing literature that has documented increases in both maternal confidence 46 and assigned importance 13 to shared reading following a shared reading intervention during the first 4 years of life. We speculate that the driver of differences found in this study may be attributable to opportunities for more frequent shared reading practice and consistent, clear anticipatory guidance provided by trusted clinicians across the 6-month intervention.…”
Section: Discussionsupporting
confidence: 93%
“…In addition to reading more often, parents in the intervention group reported significantly greater comfort reading to their infants relative to the control group, and also assigned higher importance to shared reading at this age. These findings are consistent with our hypothesis and also with existing literature that has documented increases in both maternal confidence 46 and assigned importance 13 to shared reading following a shared reading intervention during the first 4 years of life. We speculate that the driver of differences found in this study may be attributable to opportunities for more frequent shared reading practice and consistent, clear anticipatory guidance provided by trusted clinicians across the 6-month intervention.…”
Section: Discussionsupporting
confidence: 93%
“…confirm their novelty (e.g., forlorn, Beck & McKeown, 2007), sophisticated words selected to ensure their relative novelty for the target age range (e.g., departed for 4-or 6-year-olds, Houston-Price, Howe, & Lintern, 2014), or completely novel pseudowords (e.g., manu, Horst et al, 2011). Studies that used confirmed unknown words (e.g., forlorn) included pretests or pilots to determine baseline word knowledge before storybook reading (e.g., Abel & Schuele, 2014; Wilkinson & Houston-Price, 2013) and therefore did not include non-storybook reading control groups.…”
Section: Literature Search and Inclusion Criteriamentioning
confidence: 80%
“…Shared storybook reading provides several benefits to young children including parent-child bonding (Barratt-Pugh & Rohl, 2015;Schwartz, 2004), fostering a love of reading later in life (Bus, 2001;Pillinger & Wood, 2014) and learning to sustain attention (Lawson, 2012). Much of children's developing lexicon is encountered through everyday conversation (Weizman & Snow, 2001), but shared storybook reading provides a complementary source of vocabulary (Montag, Jones, & Smith, 2015).…”
Section: The Effects Of Shared Storybook Reading On Word Learning: a mentioning
confidence: 99%
“…Another study using a similar approach to the 'Let's Read' program is the 'Better Beginnings' program (Barratt-Pugh & Rohl, 2015). The 'Better Beginnings' program in Western Australia provided 300 parents of young babies (six to eight weeks old) with a reading pack through their child health nurse (Barratt-Pugh & Rohl, 2015). Parents from varying socioeconomic backgrounds participated.…”
Section: Early Storybook Reading Programs In Australiamentioning
confidence: 99%